2002
DOI: 10.1590/s1516-35982002000500019
|View full text |Cite
|
Sign up to set email alerts
|

Data de desmame e desempenho reprodutivo de vacas de corte

Abstract: RESUMO -O experimento foi conduzido na Estação Experimental Agronômica da Universidade Federal do Rio Grande do Sul, município de Eldorado do Sul, Brasil. O objetivo do estudo foi avaliar o efeito da data do desmame precoce (05/01/99) ou do convencional (26/03/99) sobre o desempenho reprodutivo de vacas de corte multíparas em duas estações de monta, 98/99, e a subseqüente, 99/00. Cinqüenta vacas tiveram seus bezerros desmamados em média aos 91 dias de vida, com peso mínimo de 70 kg (desmame precoce = DP), e 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
2
4
0
11
Order By: Relevance
“…These results are consistent with those obtained by , Moojen et al (1994), Simeone & Lobato, (1996); Restle et al (2001), and Almeida et al (2002), who found that cows submitted to early weaning presented higher pregnancy rates as compared to conventionally-weaned cows.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…These results are consistent with those obtained by , Moojen et al (1994), Simeone & Lobato, (1996); Restle et al (2001), and Almeida et al (2002), who found that cows submitted to early weaning presented higher pregnancy rates as compared to conventionally-weaned cows.…”
Section: Resultssupporting
confidence: 92%
“…This resulted in a 39-day reduction in calving interval related to better nutritional conditions as compared to 2004/2005. This is consistent with the findings by Short et al (1972) and Montiel & Ahuja (2005), who also mention that the presence of calf with the cow causes a significant increase in the duration of post-calving anestrus, and consequently, of the calving interval. Almeida et al (2002), studying early weaning at 91 days, as carried out in the first year of the present study, observed an average calving interval of 399.2 days, which is similar to the result of 397.4 days that was obtained in this study. Those authors stated that this is not an optimal interval, because to obtain one calf/year, the required interval would be ± 365 days, as verified in the second year of observation, when weaning age was reduced to 67 days.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations